2017
DOI: 10.1149/2.0331704jes
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Parasitic Heat Flow of Lithium Ion Pouch Cells Containing EC-Free Electrolytes

Abstract: A recent study has shown that removing ethylene carbonate (EC) from electrolytes in Li [Ni 0.4 Mn 0.4 Co 0.2 ]O 2 /graphite lithium ion pouch cells significantly increases the cycle life and lifetime at high voltage operation. This work investigates the performance of EC-free electrolytes by adding small amounts of electrolyte additives to 1 M LiPF 6 ethyl-methyl carbonate in Li [Ni 0.4 Mn 0.4 Co 0.2 ]O 2 /graphite pouch cells and measuring the parasitic heat flow during high voltage operation. EC-free elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…42,46 Since the entropic heat flow is reversible between charge and discharge, the average parasitic heat flow at each voltage point can be found by taking the average of charge and discharge heat flow and subtracting the average overpotential heat flow. The details of this method was introduced by S. Glazier et al 47 Figure 8a • C were observed for all the charged electrode materials and the peak intensity increases with increasing of state of charge of the electrode materials (higher upper cutoff voltage of the cells). The release of oxygen from the bulk of the charged materials is associated with the degradation of NMC532 from a layered (Li x MO 2 , M = Ni, Mn and Co) structure to a rock-salt (Li x M 1-x O) structure.…”
Section: Resultsmentioning
confidence: 99%
“…42,46 Since the entropic heat flow is reversible between charge and discharge, the average parasitic heat flow at each voltage point can be found by taking the average of charge and discharge heat flow and subtracting the average overpotential heat flow. The details of this method was introduced by S. Glazier et al 47 Figure 8a • C were observed for all the charged electrode materials and the peak intensity increases with increasing of state of charge of the electrode materials (higher upper cutoff voltage of the cells). The release of oxygen from the bulk of the charged materials is associated with the degradation of NMC532 from a layered (Li x MO 2 , M = Ni, Mn and Co) structure to a rock-salt (Li x M 1-x O) structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, these cathodes suffer from poor cyclability and thermal abuse tolerance due to their high reactivity with the commonly used ethylene carbonate (EC)‐based electrolyte solution. [ 7–11 ] As well recognized, the EC‐based electrolyte is easily oxidized on the surfaces of high nickel cathodes at high voltages, resulting in electrolyte dryout, gas evolution, and impedance growth and consequently a continuous degradation of battery performance. [ 12–14 ] On the other hand, the high melting point of EC is a major cause for the poor low temperature performance of current LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works have demonstrated that simply removal of EC from the currently used electrolytes can enable considerably improved high‐voltage cyclability and high temperature stability of LIBs. [ 9,10,12–15 ] Therefore, development of advanced electrolyte systems is crucial for overcoming the challenges of conventional EC‐based electrolyte on new LIB electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been used to determine the benefit of removing EC from NMC442/graphite cells above 4.3 V, 27,28 as well as measuring the effect of vinylene carbonate and 1-fluoro-ethlyne carbonate as electrolyte additives on the parasitic heat flow in large voltage ranges. 29 Figure 4a demonstrates this method to calculate the parasitic heat flow of one of the 442 cells during the first protocol step between 3.9 V and 4.2 V and will be called the "average method" throughout this work.…”
Section: Resultsmentioning
confidence: 99%